2015
DOI: 10.1097/eja.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Airway reactions and emergence times in general laryngeal mask airway anaesthesia

Abstract: BACKGROUNDDesflurane's short emergence time supports fast track anaesthesia. Data on the rate of upper airway complications and emergence time when desflurane is used with laryngeal mask airway (LMA) are controversial and limited.OBJECTIVESTo compare recovery time variables and the rates of upper airway adverse events in patients with an LMA undergoing general surgery with desflurane, sevoflurane, isoflurane or propofol anaesthesia.DESIGNA systematic review and meta-analysis of randomised controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 47 publications
2
42
2
1
Order By: Relevance
“…[318] Consistent with recent meta-analyses, we found that desflurane or sevoflurane use was associated with lower rates of prolonged patient emergence time versus isoflurane. [12131920]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[318] Consistent with recent meta-analyses, we found that desflurane or sevoflurane use was associated with lower rates of prolonged patient emergence time versus isoflurane. [12131920]…”
Section: Discussionmentioning
confidence: 99%
“…Of note, laryngospasm incidence does not change with the type of inhaled anesthetic administered. [20] The authors cannot exclude the possibility that unconsidered covariates, such as the history of anesthetic complications, documented difficult intubation, obstructive sleep apnea, and others may have exerted an effect on emergence time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Meta-analysis was performed by using generalised pivotal methods. 3,5 We recommend caution in relying on the accuracy of coverage, or meaningfulness of interpretation, of the confidence intervals for the recovery times in Stevanovic et al 1 Based on our statistical developments, 3,4 what are the authors' perspectives?…”
Section: Editormentioning
confidence: 96%
“…Stevanovic et al 1 performed a meta-analysis comparing multiple endpoints between desflurane and other general anaesthetic agents including sevoflurane, isoflurane and propofol. They limit consideration to patients with laryngeal mask airway.…”
Section: Editormentioning
confidence: 99%